Facile hydrothermal-carbonization approach to carbon-modified BiVO4 composites with enhanced photocatalytic activity. (July 2015) - Tang, Jianting; Song, Beibei; Deng, Qian; Xin, Hongchuan
Abstract: In this study, a series of carbon-modified BiVO4 composites were prepared by hydrothermal-carbonization method using glucose as carbonaceous resource. The composites were characterized by X-ray diffraction (XRD), ultraviolet–visible diffuse reflectance spectrum (UV–vis DRS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and photoluminescence (PL) techniques. The photocatalytic activity of the composites was evaluated in degradation of methylene blue (MB) dye under irradiation of visible light. It was found that the carbon content of the composites plays an important role in the photocatalytic degradation, and the photocatalytic activity of carbon-modified BiVO4 composites is higher than that of pure BiVO4 . The higher photocatalytic activity of the composites can be attributed to their higher adsorption capacity and higher separation efficiency of photogenerated carriers.